“Sim, Senhora! Não, Senhor!” identidade e trabalho doméstico - Oliveira, Débora Laís Silva de (2018)
This research is based on the Critical Social Psychology and aims to analyze the identity policies toward domestic workers. It aims, as well, to identify how such policies shape the praxis of daily life, understanding what could be possibilities of recognition for the worker in this context and how it would be possible to question the current praxis and reinvent labor relations. With these goals in mind, the research problem outlines as follows: Faced with identity policies and its effects on the praxis of everyday, what are the possibilities of recognition and reinvention of these praxis? The social relevance of this research demonstrates itself on the contemporaneity and magnitude of the domestic work, both in political and social terms, such as the increase of media attention and law advancement, as in quantitative terms. The methodological is based on the notion of sintagma identity-metamorphosis-emancipation, using life trajectory narrative. The remaining items are divided into two parts. The first, called "Yes, madam!", demonstrates the routes of socialization, obedience and submission and it is composed by reflections on the importance of socialization on identity formation (chapter 3). The second part, called "No, sir!", refers to the need of questioning social habits and promoting discomfort on the identity policies that have been reproduced. Chapter 5 presents buzzing and noises that the media have occasioned on regulatory identity policies. At last, the final considerations (chapter 6) draw reflections on the historical constructions of domestic work, which are imprinted in the relations on the context of such work: the naturalized invisibility, the work overload and the depreciative recognition. The necessity for a search toward social recognition, in the terms of Honneth (2003) and for the importance of domestic work were highlighted. In this direction, the vindication for more dignified work conditions, toward emancipatory possibilities, was indicated